Immature granulocyte in prediction of the short-term and long-term mortality of patients with acute myocardial infarction - GÜLTEN, Sedat; CİHAN ÇALIŞGAN, Neslihan; AKYEL, Serdar; KUKUL GÜVEN, Fatma Mutlu (The European Research Journal, 2023)
Objectives: Despite great advances in the treatment of acute myocardial infarction (AMI), it is still the most common cause of death in the world. Therefore, predicting mortality in advance is clinically very important. In this study, we aimed to investigate the role of immature granulocyte (IG) and other hematological markers in predicting short- and long-term mortality in patients with AMI. Methods: Laboratory information system (LIS) data of a tertiary hospital were used in this study. Of the 298 patients who were admitted to the coronary intensive care unit with the diagnosis of myocardial infarction, 258 recovered after treatment and were discharged. 40 of them died. It was determined that 36 of these 258 patients, who were followed up retrospectively, died within 15 months after discharge. Results: The mean age of 298 people who participated in this retrospective study was 73.26 ± 8.6 years, and 53.3% were male. Moderate and high predictive property in receiver operating characteristic (ROC) analysis for short-term mortality, white blood cell (WBC) area under curve (AUC) = 0.802), neutrophil count (AUC = 0.817), IG count (AUC = 0.841), neutrophil/lymphocyte ratio (NLR) (AUC = 0.701), and C-reactive protein (CRP) (AUC = 0.758) tests detected. For long-term mortality, a moderate predictive feature was observed in the age (AUC = 0.712) parameter. Conclusions: IG is a marker that does not require extra cost, provides rapid results and has high predictive value in predicting death in the short term in patients with acute myocardial infarction. It is ineffective in predicting long-term mortality.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer); Immature granulocyte count; acute myocardial infarction; mortality; inflammation; hematological markers; 3. Good health